Photoprotective efficacy and safety evaluation of Syzygium aqueum leaf extract in topical sunscreen formulations - Nurul Indriani; Lina Yunita (Acta Chimica Asiana, 2026)
Abstract:  Ultraviolet (UV) radiation is a major environmental hazard linked to erythema, photoaging, and skin cancers. While synthetic UV filters such as oxybenzone and octinoxate are widely used in commercial sunscreens, their potential for irritation, allergic reactions, and hormonal disruption raises safety concerns. This study aimed to develop and evaluate a sunscreen formulation using Syzygium aqueum (water apple) leaf extract, a plant rich in flavonoids, tannins, and phenolic compounds with antioxidant and UV-absorbing activity. The extract was obtained via maceration with 96% ethanol and incorporated into four cream formulations: a control without extract (F0) and three with 1%, 3%, and 5% concentrations (F1–F3). Physicochemical properties, pH, sun protection factor (SPF), and irritation potential were assessed. All formulations showed uniform consistency without phase separation, with pH values ranging from 6.3 to 6.6, which are suitable for topical application. SPF analysis revealed a concentration-dependent increase, from 7.0 in F0 to 18.0 ± 1.2 in F3, indicating enhanced photoprotective capacity. Irritation testing on  rabbits showed no erythema or edema across all samples, confirming dermatological safety. Overall, the incorporation of S. aqueum extract significantly improved UV-protective activity while maintaining skin compatibility. These findings highlight the potential of S. aqueum as a safe and effective natural sunscreen ingredient and support its application in the development of botanical-based cosmetic products.